GOALS AND OBJECTIVES OF LEARNING FOREIGN LANGUAGES IN TERMS OF CORPORATE TEACHING PROGRAMS - Potapova, E.N. (Tambov University Review. Series: Humanities, 2016)
It is devoted to the goals and objectives of learning foreign languages in terms of corporate teaching programs, which are based on the requirements of the society and the government to the skills of modern professionals. The goals are the following: 1) developing foreign language communicative competence; 2) developing intercultural communicative competence; 3) teaching foreign languages for special purposes. The objectives are outlined as follows: 1) teaching English for international communication; 2) teaching communicative skills in situations of professional interaction; 3) teaching professional skills in English; 4) developing intellectual, psychological and social competence; 5) raising motivation to learn foreign languages; 6) intensification of foreign language learning. Professional skills and qualities, which are developed by means of English and necessary for successful business performance of a person, are also outlined, they are command of special terminology, ability to speak on economic and professional topics, presentation, negotiation skills, skills of written business communication, critical thinking, creativity, skills to work with a big amount of information, ability to solve professional problems independently, ability to use knowledge from one sphere of study in another one etc. To achieve these goals and objectives the following methods and teaching technologies were selected: an interdisciplinary approach, a student-oriented approach, a technology of developing critical thinking, a method of projects, interactive computer programs, context-based approach, corporate forms of teaching, creating a foreign language corporate environment.